2017
DOI: 10.3856/vol45-issue5-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density for freshwater prawn Macrobrachium rosenbergii (Decapoda, Palaemonidae) in biofloc system

Abstract: ABSTRACT. The objective of this study was to evaluate the effect of stocking densities on productive performance of the freshwater prawn Macrobrachium rosenbergii in biofloc system. Experimental tanks (microcosms) with 0.20 m² area were used as experimental units. The tanks were connected to two 300 L matrix tanks (macrocosm) with biofloc technology, used as recirculating units. M. rosenbergii juveniles, with an initial weight of 0.315 ± 0.06 g and initial length of 33.34 ± 2.26 mm, was randomly distributed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
15
3
2
Order By: Relevance
“…The weight gain and SGR results obtained in the D50 treatment in this study were found to be superior to those recorded during the nursery stage in longarm river prawns (Vega‐Villasante et al 2011; Peña‐Herrejón et al 2019) and giant freshwater prawns (Langer et al 2011; Negrini et al 2017; Avillanosa et al 2019) in various other culture systems. The FCR was lower than that recorded in the nursery phase for longarm river prawns (Peña‐Herrejón et al 2019) and giant freshwater prawns (Negrini et al 2017), whereas the FCE was observed to be higher than that reported in other studies with peneid shrimp (Serrano and Declarador 2014). However, estimation of FCR and FCE were affected by the study system because uneaten feed was not recovered and the production of plankton and periphyton was not quantified, thereby causing an over‐ and underestimation of these parameters.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The weight gain and SGR results obtained in the D50 treatment in this study were found to be superior to those recorded during the nursery stage in longarm river prawns (Vega‐Villasante et al 2011; Peña‐Herrejón et al 2019) and giant freshwater prawns (Langer et al 2011; Negrini et al 2017; Avillanosa et al 2019) in various other culture systems. The FCR was lower than that recorded in the nursery phase for longarm river prawns (Peña‐Herrejón et al 2019) and giant freshwater prawns (Negrini et al 2017), whereas the FCE was observed to be higher than that reported in other studies with peneid shrimp (Serrano and Declarador 2014). However, estimation of FCR and FCE were affected by the study system because uneaten feed was not recovered and the production of plankton and periphyton was not quantified, thereby causing an over‐ and underestimation of these parameters.…”
Section: Discussioncontrasting
confidence: 53%
“…In terms of the intensification of culture for freshwater prawns, stocking density and culture strategies are the main factors that contribute to estimating production and survival at this higher level of culture intensity because the majority of growth performance parameters tend to be critical under these factors (Sanchez‐Zazueta et al 2013). Studies on the effect of stocking density in freshwater prawn culture have been carried out in coconut garden channels (Ranjeet and Kurup 2011), circular tubs (Langer et al 2011), fiberglass tanks (Banu et al 2016), aquarium (Costa and Arruda 2016), earthen ponds (Paul et al 2016; Chowdhury et al 2017), biofloc systems (Negrini et al 2017), and net cage–concrete pond systems (Avillanosa et al 2019) for the giant freshwater prawn. The highest productions were observed in densities ranging from 1.5 to 3.0 prawns/m 2 in semi‐intensive systems and from 5 to 50 prawns/m 2 in intensive systems.…”
mentioning
confidence: 99%
“…The BFT is being practised in semi-intensive commercial shrimp grow-out ponds and also in super-intensive tank and raceway systems, with a production of over 9 kg shrimp m À3 (Taw 2010). Shrimp survival, growth performance and health status generally decrease with increasing stocking density, as reported for white shrimp Litopenaeus vannamei (Wasielesky et al 2013;Liu et al 2017) and freshwater prawn Macrobrachium rosenbergii (Negrini et al 2017). This has been attributed mainly to increased competition for the space and food sources, cannibalism and instability in water quality (Abdussamad & Thampy 1994;Arnold et al 2005).…”
Section: Stocking Densitymentioning
confidence: 82%
“…2017) and freshwater prawn Macrobrachium rosenbergii (Negrini et al . 2017). This has been attributed mainly to increased competition for the space and food sources, cannibalism and instability in water quality (Abdussamad & Thampy 1994; Arnold et al .…”
Section: Factors Affecting Shrimp Culture In Biofloc Systemsmentioning
confidence: 99%
“…This fact was observed in the present study; our results showed that M. amazonicum individual mass had a slight reduction at the 120 shrimps treatment differing significantly (P < 0.05) of 40 shrimps treatment. In crowded conditions, conflicting results were observed in others species suggesting that in shrimps, the intraspecific competition has important paper and can influence the regulation of population, but it does not affect the weight and growth performance (El-Sherif and Mervat 2009;Paul et al 2016;Negrini et al 2017).…”
Section: Performance Shrimpmentioning
confidence: 99%